Cerebral Infiltrative Lesion and Chronic Clinical Course of the Rosai-Dorfman Disease: Case Report - nazari, shiva; Mollaei Tavana, Parastoo; Khalili, Mitra (Iranian Journal of Child Neurology, 2021)
Rosai-Dorfman disease (RDD) is a rare disorder of an unknown etiology, characterized by a benign histiocytic proliferation in the lymph nodes, as well as the extranodal sites. Painless bilateral lymphadenopathy is the classic presentation of RDD in the majorityof patients. The exteranodal disease involves the skin, soft tissues, bones, the genitourinary system, the lower respiratory tract, and the central nervous system. A seven-year-old boy was referred to our hospital with left parietal swelling, headache, fever, imbalance, weight loss, and speech and walking impairments. In early examinations, he showed a hyposignal infiltrative lesion in the lateral ventricle and the choroid plexus, expanding to the subcortical white matter of the bilateral temporooccipital areas. After surgery and sampling, he was diagnosed with cerebral RDD. According to his history, he had bilateral cervical lymphadenopathy at the age of two years, femoral soft tissueinvolvement at the age of three, and a skin disorder that improved with local treatments at the age of five. However, at the time of referral to the hospital, there were no other symptoms in other areas, except for brain symptoms. In the differential diagnosis of brain lesions with specific borders in high-contrast radiological views, the probability of RDD should be considered, similar to meningioma. The presence of painless and extensive bilateral cervical lymphadenopathy can improve the diagnosis of this disease. Isolated brain involvement in RDD is very rare, and it can be seen in less than 5% of cases. Nevertheless, by early diagnosis and intervention, the risk of complications is reduced, and the prognosis is improved.